Regional variances depict a unique glial-specific inflammatory response following closed-head injury - White, Michelle R.; VandeVord, Pamela J. (Frontiers in Cellular Neuroscience, 2023)
Abstract Mild traumatic brain injuries (mTBI) constitute a significant health concern with clinical symptoms ranging from headaches to cognitive deficits. Despite the myriad of symptoms commonly reported following this injury, there is still a lack of knowledge on the various pathophysiological changes that occur. Preclinical studies are at the forefront of discovery delineating the changes that occur within this heterogeneous injury, with the emergence of translational models such as closed-head impact models allowing for further exploration of this injury mechanism. In the current study, male rats were subjected to a closed-head controlled cortical impact (cCCI), producing a concussion (mTBI). The pathological effects of this injury were then evaluated seven days following. The results exhibited a unique glial-specific inflammatory response, with the ipsilateral and contralateral sides of the cortex and hippocampus showing pathological changes following impact. Overall these findings are consistent with glial changes reported following concussions and may contribute to subsequent symptoms.